Microstructural evolution during spark plasma sintering of TiCâAlNâgraphene ceramics - Nguyen, V.-H. (Elsevier Ltd, 2021)
This examination intended to evaluate the synergic influence of graphene nano-platelets (GNPs) and AlN on the microstructure and consolidation behavior of TiC. The spark plasma sintering (SPS) method was employed as the manufacturing process under the sintering circumstances of 40 MPa, 10 min, and 1900 Â°C. The simultaneous incorporation of AlN and GNPs could improve the relative density of TiC more than 4, reaching a fully dense ceramic. According to the X-ray diffraction (XRD) spectrum, thermodynamic study, as well as the microstructural assessments, i.e., scanning electron microscopy (SEM), Electron probe micro-analyzer (EPMA), scanning transmission electron microscopy (STEM) and transmission electron microscopy (TEM), the TiN and Al2OC ingredients were produced over the SPS process as the in-situ phases. Although Al2OC remained in the microstructure as an amorphous-like phase, the in-situ produced TiN dissolved into the TiC matrix, creating a Ti(C,N) solid solution. A chemical reaction between AlN and the surface oxide of TiC, namely TiO2, was found to be responsible for the in-situ generation of the TiN compound. Thanks to the formation of the solid solution, strong interfaces were created amongst the matrix grains, promoting the transgranular fracture mode. Moreover, some dislocations and distorted atomic planes were seen in the microstructure, derived from the thermal expansion coefficients' inconsistency between the different phases over the cooling stage. Â© 2021 Elsevier Ltd